The Relationship Between Parental Communication Patterns and Children's Personal Social Development in Post-Pandemic COVID-19 - Merina, Nuning Dwi; Sulistyorini, Lantin; Azizah, Aufa (Jurnal Kesehatan Komunitas Indonesia, 2024)
The growth and development of preschool-aged children need to be considered by parent, one of which is their personal social development. Social development at the preschool age is considered important because it will be an introduction to children's readiness to enter school. incorporating parents into the social development of pre-school age children, one of which is through good communication patterns. One of the post-pandemic conditions of COVID-19 can cause communication between parents and children to be not optimal. The research objective was to determine the readiness of parents through communication patterns as a mitigation strategy in children's social development in the post-COVID-19 pandemic. The research method uses quantitative research with a cross-sectional study approach. the study group in this study was 38 parents of children in Al-Hidayah V Kindergarten Mangli-Jember Kindergarten. Bivariate analysis using the Pearson correlation test used for this research. There is a very strong relationship between parents' communication patterns and children's social development. Parents have good readiness as a form of strategic mitigation in improving children's social development through good communication patterns in the post-COVID-19 pandemic.